The buzz in the field: the interaction between viruses, mosquitoes, and metabolism - Ratnayake, Oshani C.; Chotiwan, Nunya; Saavedra-Rodriguez, Karla; Perera, Rushika (Frontiers in Cellular and Infection Microbiology, 2023)
Among many medically important pathogens, arboviruses like dengue, Zika and chikungunya cause severe health and economic burdens especially in developing countries. These viruses are primarily vectored by mosquitoes. Having surmounted geographical barriers and threat of control strategies, these vectors continue to conquer many areas of the globe exposing more than half of the world’s population to these viruses. Unfortunately, no medical interventions have been capable so far to produce successful vaccines or antivirals against many of these viruses. Thus, vector control remains the fundamental strategy to prevent disease transmission. The long-established understanding regarding the replication of these viruses is that they reshape both human and mosquito host cellular membranes upon infection for their replicative benefit. This leads to or is a result of significant alterations in lipid metabolism. Metabolism involves complex chemical reactions in the body that are essential for general physiological functions and survival of an organism. Finely tuned metabolic homeostases are maintained in healthy organisms. However, a simple stimulus like a viral infection can alter this homeostatic landscape driving considerable phenotypic change. Better comprehension of these mechanisms can serve as innovative control strategies against these vectors and viruses. Here, we review the metabolic basis of fundamental mosquito biology and virus-vector interactions. The cited work provides compelling evidence that targeting metabolism can be a paradigm shift and provide potent tools for vector control as well as tools to answer many unresolved questions and gaps in the field of arbovirology.